2022
DOI: 10.1371/journal.pone.0277645
|View full text |Cite
|
Sign up to set email alerts
|

Moving online: Experiences and potential benefits of digital dance for older adults and people with Parkinson’s disease

Abstract: Background Dance provides a range of beneficial effects for older adults including individuals with age-related neurological conditions such as Parkinson’s disease (PD). The COVID-19 pandemic accelerated the development of at-home dance programs delivered digitally through live and pre-recorded media, but little is known about how participants may engage with and benefit from these resources. Objective This study explored experiences and potential benefits of digital dance participation among healthy older a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Most participants perceived benefits (ie, to mood and perceived energy), which corroborates previous studies. [20][21][22] There were perceived benefits for older adults without PD as well, and the presence of older adults in this format did not cause any issues for the PD population. Nonetheless, social interaction varied between the groups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Most participants perceived benefits (ie, to mood and perceived energy), which corroborates previous studies. [20][21][22] There were perceived benefits for older adults without PD as well, and the presence of older adults in this format did not cause any issues for the PD population. Nonetheless, social interaction varied between the groups.…”
Section: Discussionmentioning
confidence: 89%
“…2,6,[17][18][19] Recently, a previous observational study investigated the perceptions of people with PD who were active or interested in digital home-based dancing (synchronous and asynchronous). 20,21 The participants' perceptions included physical and non-physical benefits. Over a third of participants were not using digital resources due to a lack of motivation and/or knowledge on accessing online resources, 20 although dance at home appeared to be engaging and accessible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PwP also reported that they streamed their music (52%), and slightly more used a personal listening device (56%, mostly their phone) or used smart technology (34%) such as Amazon Alexa. Such as range of listening technologies could be expected as other studies show that PwP engage with interventions that are delivered online and that these can be effective and are highly valued (Bek et al, 2021a(Bek et al, , 2021b(Bek et al, , 2022Morris et al, 2021). Nevertheless, future studies should specifically evaluate how technology relates to musical engagement as has been conducted in other fields (e.g., Creech, 2019;MacRitchie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Dance interventions not only address mobility issues, but also promote cognition, emotional expression, kinesthetic awareness, and social engagement ( Hwang and Braun, 2015 ; Clifford et al, 2023 ). During the COVID-19 pandemic, many dance therapy classes moved online, which afforded the convenience and safety of participating from one’s own home but removed elements of social interaction and group support that are naturally structured into in-person classes ( Bek et al, 2022 ). Kinesthetic empathy, or the ability to perceive others’ emotions through action observation, is a key component of in-person classes ( Christopher and Tamplin, 2022 ) that may occur less spontaneously during virtual classes.…”
Section: Introductionmentioning
confidence: 99%